Pulmonary Alveolar Microlithiasis: A commonly misdiagnosed rare entity - Alkesh Khurana; Rajesh Malik; Jitendra Sharma; Ujjawal Khurana; Abhishek Goyal (Sultan Qaboos University Medical Journal, 2018)
Pulmonary alveolar microlithiasis (PAM) is an uncommon entity which can pose a diagnostic challenge. We report a 45-year-old female who was referred to the All India Institute of Medical Sciences, Bhopal, India, in 2017 with a two-year history of progressively worsening dyspnoea and dry coughing. She had been previously diagnosed with pulmonary tuberculosis elsewhere and prescribed antitubercular therapy; however, there was little improvement in her symptoms. Following referral, the patient was diagnosed with PAM based on high-resolution computed tomography findings and the abundance of lamellar microliths in a bronchoalveolar lavage sample. She was subsequently managed symptomatically and enrolled in a rehabilitation programme.